5 - Epistemological Issues in the Making of an African medicine: Sutherlandia (Lessertia Frutescens) - Olajide Oloyede, (African Sociological Review, 2010)
The scientific clinical trial of the African traditional medicine, Sutherlandia (Lessertia fru- tescens) forms an interface between the indigenous local knowledge of people living with Aids, traditional health practitioners and that of science and global health. up till now, no cross-disciplinary studies have been done on epistemological questions concerning especially the knowledge and understanding of ‘proof ’ of efficacy concerning an African traditional medicine. This paper draws together insights and analysis from the anthropology and sociology of health and healing in discussing the intersecting fields of knowledge and experience of pharmacology, phytotherapy and related fields, as well as that of biomedical and traditional health practitio- ners, and of research subjects involved in the making of clinical trials of sutherlandia (lessertia frutescens) in South Africa.